UK DNA working group eDNA week, January 2022 - Lori Lawson Handley; Tabitha Blackwell; Holly A. Broadhurst; Katie Clark; Phil I. Davison; Judy England; Stefano Mariani; Allan D. McDevitt; Kirthana Pillay; Dan Read; Kerry Walsh; Andy Nisbet; et al. (Environmental DNA, 2023)
Abstract Here, we report on eDNA week, an international conference held online as a five‐day series of webinars from January 17, 2022, to January 21, 2022. The conference was organized by the UK DNA working group, which has witnessed considerable growth and application of eDNA research since its founding and first conference in 2014. The 2022 event, held online due to the COVID‐19 pandemic, provided an opportunity to invite international researchers who are leading the field, without the usual constraints of conference location. Compared with the previous UK‐based in‐person conferences, there was greater international participation amongst the 514 people who registered to attend the event. To emphasize the importance of collaboration between sectors in driving forward DNA monitoring, a session was devoted to presentations by participants from governmental agencies, and another to those from commercial companies developing and utilizing DNA tools. The industry and stakeholder sessions were accompanied by state‐of‐the‐art presentations delivered by a global group of DNA/eDNA researchers from 11 countries. These sessions were complemented by an open forum session for reflection and discussion.